2008
DOI: 10.1007/s10654-008-9225-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of hip fracture incidence and intake of calcium, magnesium, vitamin D, and vitamin K

Abstract: The significant correlation between hip fracture incidence and vitamin K intake, and also regional variations in food patterns, suggest that increasing intake of vegetables and legumes might lead to a decrease in hip fracture incidence in the future. Further, this study suggests that a review of the dietary reference value of vitamin K from the perspective of osteoporosis would be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 18 publications
3
54
0
14
Order By: Relevance
“…According to the 2002 National Nutrition Survey in Japan, intake of these nutrients required for normal bone metabolism was lower in skippers than in nonskippers [30]. In addition, higher incidence of hip fracture was associated with low intake of vitamins D and K in both men and women [31]. Based on these studies, we speculate that skipping meals may cause nutritional deficiencies that affect bone metabolism.…”
Section: Discussionmentioning
confidence: 79%
“…According to the 2002 National Nutrition Survey in Japan, intake of these nutrients required for normal bone metabolism was lower in skippers than in nonskippers [30]. In addition, higher incidence of hip fracture was associated with low intake of vitamins D and K in both men and women [31]. Based on these studies, we speculate that skipping meals may cause nutritional deficiencies that affect bone metabolism.…”
Section: Discussionmentioning
confidence: 79%
“…Later, among several nutrients including vitamin D and calcium, vitamin K was shown to be the only nutrient that is significantly correlated with hip fracture incidence in Japanese population [14]. Furthermore, the fracture-preventing effect of vitamin K was observed in several clinical studies in Japan, which was confirmed by meta-analysis [15].…”
Section: Vitamin K2 -Vital For Health and Wellbeingmentioning
confidence: 90%
“…Some studies also found an association with BMD in younger women [113][114] . Study results are mixed with respect to intake and fracture risk 84,110,115 and among Japanese subjects low serum magnesium was associated with increased fracture incidence 116 . Short term intervention studies Mechanism by which high serum phosphate (P) impacts the parathyroid gland and kidney to lower serum P…”
Section: Bonementioning
confidence: 99%
“…A 2006 systematic review and more recent studies of older adults showed that a vitamin D intake of ≥400 IU/d was associated with reduced bone loss [150][151][152] but with respect to fracture incidence, there appears to be little association with vitamin D intake 115 . Two large reviews found that in older adults, serum 25(OH)D was positively associated with BMD but there was inconsistent evidence for an association with fractures 153. In elderly postmenopausal women, those with serum 25(OH) D levels <50 nmol/L had increased fracture risk, bone loss and mortality, leading to recommendations that 50nmol/L should be the minimum level to ensure optimum bone health, below which supplementation is recommended at 800-1000IU/d but above Mechanism by which high serum phosphate (P) triggers release of FGF23 to lower serum P this threshold there was no clear evidence for additional benefit except in fragile elderly subjects, for whom serum 25(OH) D should be ≥75nmol/l 154 .…”
Section: Bonementioning
confidence: 99%